2014
DOI: 10.1093/mp/ssu090
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Single-Nucleotide Mutation in a CLAVATA3 Gene Homolog Controls a Multilocular Silique Trait in Brassica rapa L.

Abstract: Analogs of the CLV3 peptide: synthesis and structure-activity relationships focused on proline residues. Plant Cell Physiol. 52, 30-36.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 12 publications
0
62
2
3
Order By: Relevance
“…All clv1 mutants in Arabidopsis exhibited weak, intermediate or strong multilocular phenotypes 27 , and previous studies had shown that most Brassicas plants with multiloculus had variable valve numbers in the siliques of the same plant 10, 11 . However, in this study, J163-4 planted in both central and northwestern China exhibited four valves stably in trilocular siliques.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…All clv1 mutants in Arabidopsis exhibited weak, intermediate or strong multilocular phenotypes 27 , and previous studies had shown that most Brassicas plants with multiloculus had variable valve numbers in the siliques of the same plant 10, 11 . However, in this study, J163-4 planted in both central and northwestern China exhibited four valves stably in trilocular siliques.…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, all the clv1 mutants with intermediate and strong multilocular phenotypes were dominant negative, and the mutant of CLV1 homologous gene in tomato was also expected to be dominant-negative 16, 27 . Similarly, most of the mutants with multiloculus discovered in Brassicas showed variable valve numbers 10, 11 . However, it has been unknown whether the molecular mechanism controlling multiloculus is similar between Arabidopsis and Brassicas or the dominant-negative character is associated with the instability of multilocular silique trait.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…We have shown that B. rapa harbouring loss‐of‐function clv3 alleles produces more locules and higher seed yield (Fan et al ., ). Thus, modifications of CLV3 in B. napus may provide an opportunity to breed high‐yield varieties.…”
Section: Resultsmentioning
confidence: 97%
“…SlWUS is a candidate for the lc QTL, and fas was recently found to be caused by a genomic rearrangement that alters the expression of SlCLV3 (Muños et al, 2011;Xu et al, 2015). Similarly, a naturally occurring CLV3 mutation in mustard (Brassica rapa) corresponds to the Multilocular (more than two carpels) locus, which increases seed production (Fan et al, 2014). These diverse examples indicate that CLV-WUS genes have been selected in diverse crops during domestication, and could provide further crop yield increases -for example, by engineering weak alleles using CRISPR.…”
Section: Potential Applications In Agriculturementioning
confidence: 99%